Sustained impact of holistic specimens for mammalogy and parasitology in South America: Sydney Andersonâ€™s legacy - Dunnum, Jonathan; Malaney, Jason; Cook, Joseph (THERYA, 2020)
Sydney Anderson and the "Mammalian Diversity in Bolivia" (MDB) project (1984-1993) established a highly productive model for integrated specimen-based field expeditions. We assess the extended impact of that decade-long series of holistic surveys of mammalian diversity as a productive model for building enduring and highly integrated infrastructure for biodiversity research. We point to specific examples of impact, but more generally make a case for Sydney Andersonâ€™s prescient view that collections, over time, become ever more powerful and essential scientific tools for understanding mammalian diversity and our rapidly changing planet. To assess the number of specimens held in collections and their availability for spatial analyses, we queried the Global Biodiversity Information Facility (GBIF) for Bolivian specimens. Results were downloaded and non-georeferenced specimens were georeferenced in GeoLocate. Publications utilizing specimens or data from the MDB project were identified in Google Scholar, these were used to build a citation profile to analyze impact and breadth of research. Over the course of the decade-long MDB project ca. 10,000 new â€œholisticâ€ specimens were added to natural history collections in Bolivia and the United States. These specimens and data were used in over 500 papers across a broad range of research areas, including new records for the country, and many descriptions of mammals (nine) and parasites (34) new to science. The Google Scholar profile generated for these publications has more than 20,000 citations and a citation H-index = 68 and an i-10 = 340. Sydney Andersonâ€™s legacy will endure through the exceptional collections he helped to build and the wide array of students he helped to inspire. As societal concerns related to environmental change (e. g., biological annihilation, climate change, emerging zoonotic pathogens) become more pressing, scientific questions evolve, and technology continues to develop, these critical resources will be called upon more and more frequently. Thus we can confidently predict that the value and use of the Bolivian mammal specimens archived under Syd Andersonâ€™s leadership will continue to increase in the future.